Cinema and the Festivalization of Capitalism The Experience-Makers - Vogel, Ann (Brill, 2023)
Film festivals around the world are in the business of making experiences for audiences, elites, industry, professionals, and even future cultural workers. Cinema and the Festivalization of Capitalism explains why these non-profit organizations work as they do: by attracting people who work for free, while appealing to businesses and policymakers as a cheap means to illuminate the creative city and draw attention to film art. Ann Vogel's unprecedented systematic sociological analysis thus provides firm evidence for the 'festival effect', which situates the festival as a key intermediary in cinema value chains, yet also demonstrates the impact of such event culture on cultural workers' lives. By probing the various resources and institutional pillars ensuring that the festivalization of capitalism is here to stay, Vogel urges us to think critically about publicly displayed benevolence in the context of cinema-and beyond.